2003
DOI: 10.1002/path.1359
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amplicon boundaries at 20q13.2 in tissue samples of human gastric adenocarcinomas by high‐resolution microarray comparative genomic hybridization

Abstract: Comparative genomic hybridization (CGH) of gastric adenocarcinomas frequently shows gains and amplifications of chromosome 20. However, the underlying genetic lesion is unknown and conventional CGH results do not allow specification of the target region. In order to investigate this chromosomal aberration with a higher resolution and sensitivity, microarray-based CGH was performed with both scanning and high-resolution arrays of chromosome 20 in a series of 27 gastric adenocarcinomas. Locus-specific fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 46 publications
0
63
1
Order By: Relevance
“…This could be explained by higher tumour heterogeneity in gastric and colorectal cancer than in breast cancer. Fluorescence in situ hybridization experiments on gastric cancers on chromosome 20q support this idea (Weiss et al, 2003). Given their clinical relevance, a biological significance of these low-level changes must exist, but their effect in terms of gene expression remains to be determined.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could be explained by higher tumour heterogeneity in gastric and colorectal cancer than in breast cancer. Fluorescence in situ hybridization experiments on gastric cancers on chromosome 20q support this idea (Weiss et al, 2003). Given their clinical relevance, a biological significance of these low-level changes must exist, but their effect in terms of gene expression remains to be determined.…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of substantially larger series of cases will enable to narrow down the common regions of overlap for these discriminating chromosomal loci, which can then be explored with contig arrays. These contig arrays may reveal amplifications within such a common region of interest that otherwise could have been missed, and this can be a strong indication of the actual genes involved (Varis et al, 2002;Weiss et al, 2003). By means of fluorescent in situ hybridization analysis and expression analysis, these candidate genes can be validated (Varis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…45 In our study, gain of 20q was detected in 71 cases (70%) and was associated with the pattern of the cancer-stroma 51 and CYP24 (20q13.2). 52 Amplification and overexpression of the BTAK gene, which encodes breast tumor-amplified kinase (identical to aurora2, ARK1 and STK15), have been reported in primary gastric adenocarcinomas that were associated with aneuploidy and poor prognosis. 47 Moreover, amplification and overexpression of the AIB1 (amplified in breast cancer 1) gene, a member of the steroid receptor coactivator family, appears to be useful as a marker of poor prognosis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was also been reported that the ZNF217 gene, which encodes a transcription factor, and the CYP24 gene, for a suppressor of the active form of vitamin D that inhibits cell growth, at 20q13.2 might be relevant to gastric carcinogenesis. 52 Thus, expressions of these genes at 20q12-13 are likely regulated not only by amplifications of these genes but also by other mechanisms such as transcriptional activation, and expressions of these genes might play an important role in the development and progression of gastric cancers. A gain in DNA copy number at 8q was the second most frequent gain, but it was not associated with clinicopathologic factors in our series.…”
Section: Discussionmentioning
confidence: 99%
“…For the sex chromosomes, a log 2 ratio of 0.22-0.28 was suggested for a single copy change [29,30]. With an indirect study design, ranges of 0.2-0.6 had been suggested for a single copy change [31,32] and a log 2 ratio of 0.68 was suggested as the criterion for genome alterations, such as duplicated or deleted gene changes, regardless of differences in microarray study design (direct, indirect, sex-matched, sex-mismatched; Fig. 3) [28].…”
Section: Pharmacogenomic Study Using Cdna Microarray Cghmentioning
confidence: 99%